Risk behaviours among female sex workers in China: a systematic review and data synthesis. - Eric P F Chow; Kathryn E Muessig; Lei Yuan; Yanjie Wang; Xiaohu Zhang; Rui Zhao; Peng Sun; Xiaoshu Sun; Joseph D Tucker; Jun Jing; Lei Zhang (PLoS ONE)
Background Commercial sex is one of the major modes of HIV transmission in China. Understanding HIV risk behaviours in female sex workers (FSW) is of great importance for prevention. This study aims to assess the magnitude and temporal changes of risk behaviours in Chinese FSW. Method Five electronic databases were searched to identify peer-reviewed English and Chinese language articles published between January 2000 and December 2012 that reported risk behaviours among FSW in China, including condom use, HIV testing, and drug use. Linear regression and Spearman's rank correlation were used to examine temporal trends in these risk factors. The study followed PRISMA guidelines for meta-analyses and was registered in the PROSPERO database for systematic reviews. Results A total of 583 articles (44 English, 539 Chinese) investigating 594,583 Chinese FSW were included in this review. At last sex, condom use was highest with commercial partners (clients), increasing from 53.7% in 2000 to 84.9% in 2011. During this same time period, condom use increased with regular partners from 15.2% to 40.4% and with unspecified partners from 38.6% to 82.5%. Increasing trends were also found in the proportion of sampled FSW who reported testing for HIV in the past 12 months (from 3.2% in 2000 to 48.0% in 2011), while drug use behaviours decreased significantly from 10.9% to 2.6%. Conclusion During the first decade of 2000, Chinese FSWs' self-reported risk behaviours have decreased significantly while HIV testing has increased. Further outreach and intervention efforts are needed to encourage condom use with regular partners, continue promotion of HIV testing, and provide resources for the most vulnerable FSW, particularly low tier FSW, who may have limited access to sexual health and prevention programs.